HUMAN RESOURCE MANAGEMENT STRATEGIES FOR GEN Z WORKFORCE ENGAGEMENT - Maulid Sakaria (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
The changing demographic composition of the modern workforce has introduced Generation Z (Gen Z) as a dominant and uniquely characterized workforce group. As digital natives, Gen Z exhibits a high preference for work flexibility, technology utilization, collaborative work environments, and organizational process involvement. This research aims to identify and analyze relevant human resource management (HRM) strategies to improve the engagement of Gen Z in the workplace. Using a systematic literature review approach, this study examines various scientific publications from 2015 to 2025 that discuss the relationship between HRM and Gen Z engagement. The study results show that effective HRM strategies consist of three main pillars: (1) value-based recruitment and employer branding strategies that emphasize transparency, flexibility, and social responsibility; (2) technology-based development and training strategies such as microlearning, e-learning, and gamification that are suitable for Gen Z's learning style; and (3) retention strategies built through an inclusive work culture, continuous feedback systems, supportive leadership, and attention to employee well-being. These findings suggest that an adaptive, contextual, and value-based approach to human resource management is key to retaining and optimizing the potential of the Gen Z workforce. The study also recommends further empirical research to test the effectiveness of these strategies in various organizational contexts.